International comovements, business cycle and inflation: A historical perspective - Haroon Mumtaz; Saverio Simonelli; Paolo Surico (Bank of England, External Monetary Policy Committee Unit, 2009)
Using a dynamic factor model, we uncover four main empirical regularities on international comovements in a long-run panel of real and nominal variables. First, the contribution of world comovements to domestic output growth has decreased over the post-WWII period. The contribution of regional comovements, however, has increased significantly. Second, the share of inflation variation due to a global factor has become larger since 1985. Third, over most of the post-WWII period, international comovements within regions have accounted for the bulk of fluctuations in business cycle and inflation. Fourth, prices have become significantly less countercyclical during the post-1984 sample, with the largest contribution due to external developments.
Keywords: E30; F40; N10; 330; output growth; inflation; geographic identification; dynamic factor model; Konjunkturzusammenhang; Wirtschaftswachstum; Inflationsrate; Wirtschaftsgeschichte; Welt